2018
DOI: 10.3390/genes9070329
|View full text |Cite
|
Sign up to set email alerts
|

Above the Epitranscriptome: RNA Modifications and Stem Cell Identity

Abstract: Sequence databases and transcriptome-wide mapping have revealed different reversible and dynamic chemical modifications of the nitrogen bases of RNA molecules. Modifications occur in coding RNAs and noncoding-RNAs post-transcriptionally and they can influence the RNA structure, metabolism, and function. The result is the expansion of the variety of the transcriptome. In fact, depending on the type of modification, RNA molecules enter into a specific program exerting the role of the player or/and the target in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 245 publications
(342 reference statements)
0
32
0
Order By: Relevance
“…Neural stem cells maintain cell populations through self-renewal, and can differentiate into various nerve cells such as neurons, astrocytes, and oligodendrocytes [64][65][66][67]. A number of studies have shown that the mRNA m 6 A modification can affect the self-renewal and differentiation of neural stem cells [68][69][70].…”
Section: Effect Of M 6 a On Neural Stem Cellsmentioning
confidence: 99%
“…Neural stem cells maintain cell populations through self-renewal, and can differentiate into various nerve cells such as neurons, astrocytes, and oligodendrocytes [64][65][66][67]. A number of studies have shown that the mRNA m 6 A modification can affect the self-renewal and differentiation of neural stem cells [68][69][70].…”
Section: Effect Of M 6 a On Neural Stem Cellsmentioning
confidence: 99%
“…RNA modification, represented by the epitranscriptome [1], refers to biochemical modifications of RNAs that are involved in functional regulations such as translation efficiency and mRNA stability without a change in the RNA sequence. Over 100 types of RNA modifications have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advent and development of high-throughput sequencing technologies coupled with direct RNA-sequencing technologies, the focus has shifted to the study of epigenetic modifications of RNA [3,4]. Based on these sequencing technologies, published data reveals that RNA contains multiple dynamic modifications, among which the most studied are N6-methyladenosine (m 6 A), 5-methylcytosine (m 5 C), N1-methyladenosine (m 1 A), N7methylguanosine(N 7 G), and ribose 2'-O-methylation as well as pseudouridine (Ψ) and inosine (I) [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%